1996
DOI: 10.1016/0014-5793(96)00250-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of presenilin‐1 expression in the mouse brain

Abstract: ). In order to study the localization of PS-1 in the brain, we raised a polyclonal antiserum specific to a fragment of the predicted protein sequence of PS-1. PS-1 immunostaining was found intracellulady, in the perikaria of discrete cells, mostly neurons, appearing as thick granules, resembling large-size vesicles. These granules were located in the periphery of cell bodies and extended into dendrites and neurites. PS-1 expression was found to be broadly distributed throughout the mouse brain, not only in str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 9 publications
8
21
0
Order By: Relevance
“…These posttranslational modifications are thereby also excluded as contributing to the formation of the high molecular mass, SDS-resistant aggregates (100 -250 kDa) in SDS-PAGE electrophoresis. These aggregates were observed to a variable extent in all our experiments, and were noticed by others using other cell types or brain tissue (36,38,39). Since the smears were detected with three different antibodies recognizing three different epitopes, and by a Myc-directed mAb using a Myctagged PS1 construct, the aggregates must contain presenilin core proteins, alone or associated with unidentified components.…”
Section: Discussionsupporting
confidence: 78%
“…These posttranslational modifications are thereby also excluded as contributing to the formation of the high molecular mass, SDS-resistant aggregates (100 -250 kDa) in SDS-PAGE electrophoresis. These aggregates were observed to a variable extent in all our experiments, and were noticed by others using other cell types or brain tissue (36,38,39). Since the smears were detected with three different antibodies recognizing three different epitopes, and by a Myc-directed mAb using a Myctagged PS1 construct, the aggregates must contain presenilin core proteins, alone or associated with unidentified components.…”
Section: Discussionsupporting
confidence: 78%
“…The major immunoreactive protein was ϳ49 kDa. This is somewhat smaller than the predicted size of the full-length protein encoded by the PS1 cDNA (467 amino acids, M r 52,664; Sherrington et al, 1995), but it is similar to the M r of PS1 recently reported by others, using antibodies to the loop region and different epitopes at the N terminus (Elder et al, 1996;Mercken et al, 1996;Moussaoui et al, 1996;Thinakaran et al, 1996). Less intense immunoreactive bands of ϳ32 and ϳ26 kDa were also present in the PS1 translation products.…”
Section: Specificity Of a Monoclonal Antibody To The N Terminus Of Ps1supporting
confidence: 75%
“…Moreover, mutations in PS1 seem to alter the endoproteolytic processing, leading to an abnormal accumulation of the full-length protein Thinakaran et al, 1996). The light microscopic distribution of native PS1 in mouse brain (Elder et al, 1996;Moussaoui et al, 1996) and the localization of epitopetagged presenilins in transfected cells (Kovacs et al, 1996) have been reported. However, little is known about the presenilin proteins in primates.…”
Section: Abstract: Presenilin; Alzheimer's Disease; Immunocytochemismentioning
confidence: 99%
“…First, message for PS2 showed a laminar distribution in cerebral cortex and was primarily detectable in neurons. This result is consistent with previous reports from normal human temporal lobes for PS2 expression visualized by radioactive hybridization [17] and is also comparable with PS1 expression pattern in murine brain observed using non-radioactive hybridization and immunohistochemistry [14,18]. Second, stronger hybridization signal was found in large neurons while mild or weak signal appeared in small neurons.…”
Section: Discussionsupporting
confidence: 92%